Shape‐Controlled Solution‐Epitaxial Perovskite Micro‐Crystal Lasers Rivaling Vapor Deposited Ones. (1st September 2022) - Afify, Hany A.; Rehm, Viktor; Barabash, Anastasiia; These, Albert; Zhang, Jiyun; Osvet, Andres; Schüßlbauer, Christoph; Thiel, Dominik; Ullrich, Tobias; Dierner, Martin; Przybilla, Thomas; Will, Johannes; et al.
Abstract: Epitaxial growth methods usually need dedicated equipment, high energy consumption to maintain pure vacuum conditions and evaporation of source materials, and elevated substrate temperatures. Solution epitaxial growth requires nothing of that but is rarely used because the achieved microstructures are of low quality, not homogeneous, and finally exhibit worse performances in devices. Here, an antisolvent‐vapor‐assisted‐crystallization of metal‐halide‐perovskites as a method overcoming these disadvantages is demonstrated. The methylammonium lead tribromide exhibits van‐der‐Waals type of epitaxial growth on mica substrates, resulting in micro‐crystallites whose shape can be controlled to be either triangular micro‐prism or micro‐cuboid. These micro‐crystallites act as optical resonators supporting various optical modes and lasing is achieved under optical excitation with low thresholds and record high environmental stability. Selecting suitable resonators from a large variety of sizes allows control of mode spacing and finally mono‐mode operation, considered to be an important feature of semiconductor laser devices. The achieved results are essentially competitive to those obtained by vapor phase epitaxial microstructures, highlighting that epitaxy of high‐quality optoelectronic device structures is feasible by minimum technological efforts and energy consumption, which are of increasing importance considering issues such as global warming and the current energy crisis. Abstract : Epitaxial micro‐resonators are grown from methylammonium lead bromide from solutions. Two different resonator geometries are reproducibly obtained on mica substrates. The micro‐resonator structures exhibit perfectly smooth surfaces and edges; exhibit lasing with low thresholds, high stability, and monomode operation and thus are of equal quality as those from vapor phase epitaxial growth.